IMPLEMENTASI MODEL MANAJEMEN KASUS DALAM MENINGKATKAN KOORDINASI PERAWATAN PASIEN DI RUMAH SAKIT - Andi, Muhammad Alwi; Arham, Afif Hidayatul (Jurnal Borneo Cendekia, 2024)
This study examines the implementation of a case management model aimed at improving patient care coordination in hospitals. Case management is a structured approach designed to ensure that patients receive comprehensive and coordinated care. The study employs qualitative methods, including in-depth interviews, participatory observation, and document analysis. Participants include case managers, nurses, doctors, and patients at Hospital X. The findings reveal that implementing the case management model significantly enhances the efficiency and effectiveness of patient care coordination. Identified benefits include improved communication among medical teams, reduced service duplication, and better continuity of patient care. Additionally, the model aids in better health resource management and facilitates more systematic monitoring of patient progress. However, challenges such as resistance to change from medical staff and limitations in human and technological resources were noted. The study concludes that with proper training and adaptation strategies, the case management model can be widely adopted to improve the quality of patient care in hospitals.